Interatividade e perspectivas no telejornalismo da TV digital - Pereira, Lívia Cirne de Azevêdo (2010)
In Brazil, the TV news had its origins in 1950, in a simple struture, without many audiovisual resources. However, as time goes by, transformations get introduced in the production of TV journalism, proved principally by the following characteristics: the use of the videotape, the emission of contents at a distance, the diffusion in colors, the beginning of the TV by subscription, the appearing of the Internet. Such innovations ensure the advent of the new technologies for a proper television, as a result, the development of the TV journalism, pushing it to revise its concepts and paradigms. An example that certificates this issue is the fact that the TV news show the need of the establishment of new formats, making available the spectator participation, based on the interactive assumption of the cyberspace, encouraging potential of content, where is valued the Internet user autonomy. In the meantime, could be said that this participation still find limitations in the analog technology, what push us to mention that to have the dialogue between the transmitter and the audience, this has to cover the other coexisting medias. In this context, the Brazilian digital TV had its origins, one media with a resolution superior than the one of the conventional TV and that allow the simultaneous emission of more information and interactive services, been these principals differentials, enabling to the users experiences more ―actuating‖, revealing inclusive, the unidirectional nature of the television. In this type of TV, the digital TV journalism, already operating in many countries, is multimedia, interactive and multidimensional. Because so, this dissertation proposal intent to produce reflections about the journalism to be disseminated by this new TV, recently even in Brazil, pointing the perspectives of development of interactive platforms.